The Potential of Metarhizium anisopliae Blastospores to Control Aedes aegypti Larvae in the Field - Tariq Butt (Journal of Fungi, 2023)
Entomopathogenic fungi are promising as an environmentally benign alternative to chemical pesticides for mosquito control. The current study investigated the virulence of Metarhizium anisopliae blastospores against Aedes aegypti under both laboratory and field conditions. Virulence bioassays of conidia and blastospores were conducted in the laboratory, while field simulation bioassays were conducted under two conditions: totally shaded (TS) or partially shaded (PS). In the first bioassay (zero h), the larvae were added to the cups shortly after the preparation of the blastospores, and in the subsequent assays, larvae were added to the cups 3, 6, 9, and 12 days later. The survival of the larvae exposed to blastospores in the laboratory was zero on day two, as was the case for the larvae exposed to conidia on the sixth day. Under TS conditions, zero survival was seen on the third day of the bioassay. Under PS conditions, low survival rates were recorded on day 7. For the persistence bioassay under PS conditions, low survival rates were also observed. Metarhizium anisopliae blastospores were more virulent to Ae. aegypti larvae than conidia in the laboratory. Blastospores remained virulent under field simulation conditions. However, virulence rapidly declined from the third day of field bioassays. Formulating blastospores in vegetable oil could protect these propagules when applied under adverse conditions. This is the first time that blastospores have been tested against mosquito larvae under simulated field conditions, and the current study could be the basis for the development of a new biological control agent.